Pengaruh Brand Image, Persepsi Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan - Witama, Alex (Universitas Tarumanagara, 2019)
It has often been argued that customer satisfaction can contribute significantly to a company?s success in a variety of ways. This study aims to analyze the effect of brand image, perceived price and service quality on customer satisfaction. The method of data collection is convenience sampling. The samples of this research are collected from 109 respondents, who are the customers in one of the biggest smartphone service center in Jakarta. The technique of data analysis used in this study was regression analysis. The result is: the relationship between brand image, perceived price and service quality have a significant and positive impact toward customer satisfaction.